Implementation of Minimum Antenatal Care Service Standards in North Lampung Regency - Suarni, Lisa; Kodri, Kodri; Aliyanto, Warjidin; Primadila, Hasti; Wahyudi, Fajar Desma (Poltekkes Kemenkes Tanjung Karang, 2024)
Maternal Mortality Rate (MMR) in North Lampung is high. Coverage of antenatal care visits in 2021 (88.7%) has yet to reach the target (100%), even though the number of midwives and integrated health post (Posyandu) services increases every year. The Minimum Service Standard report also indicates that the budget for maternal care services is around 17% of the total budget allocation. This study aims to provide an overview of the implementation of the 10 Antenatal Care (ANC) services in North Lampung. The research design employs a quantitative method with a documentation study using Maternal and Child Health (MCH) books and questionnaires to measure midwives' knowledge in North Lampung. The sample size was determined using the open-source calculator SSPropor (OpenEpi, version 3), resulting in 595 collected samples for this study. Data were analyzed using univariate and bivariate analyses. None (0%) of the pregnant women received all 10 ANC services. Almost all pregnant women (>90%) received blood pressure examinations, counseling, and referral services. Meanwhile, the ANC service received least frequently (<50%) was the provision of Iron and Folic Acid (IFA) tablets. There is a significant difference in the mean coverage based on the three clusters, and there is a weak relationship between Midwives' Knowledge and the implementation of 10 ANC services. Recommendations: There is a need for programs to comprehensively improve knowledge about ANC standards among health workers and volunteers. Discipline in recording needs to be enhanced. Further qualitative studies are required to gain a broader perspective.